EGR1 Regulates Transcription Downstream of Mechanical Signals during Tendon Formation and Healing - Gaut, Ludovic (PLoS One, 2016)
BACKGROUND: Tendon is a mechanical tissue that transmits forces generated by muscle to bone in order to allow body motion. The molecular pathways that sense mechanical forces during tendon formation, homeostasis and repair are not known. EGR1 is a mechanosensitive transcription factor involved in tendon formation, homeostasis and repair. We hypothesized that EGR1 senses mechanical signals to promote tendon gene expression. METHODOLOGY/PRINCIPAL FINDINGS: Using in vitro and in vivo models, we show that the expression of Egr1 and tendon genes is downregulated in 3D-engineered tendons made of mesenchymal stem cells when tension is released as well as in tendon homeostasis and healing when mechanical signals are reduced. We further demonstrate that EGR1 overexpression prevents tendon gene downregulation in 3D-engineered tendons when tension is released. Lastly, ultrasound and microbubbles mediated EGR1 overexpression prevents the downregulation of tendon gene expression during tendon healing in reduced load conditions. CONCLUSION/SIGNIFICANCE: These results show that Egr1 expression is sensitive to mechanical signals in tendon cells. Moreover, EGR1 overexpression prevents the downregulation of tendon gene expression in the absence of mechanical signals in 3D-engineered tendons and tendon healing. These results show that EGR1 induces a transcriptional response downstream of mechanical signals in tendon cells and open new avenues to use EGR1 to promote tendon healing in reduced load conditions.